Validity and reliability of the Dutch translation of the OPUS’ client satisfaction with device module in chronic users of hand orthoses - Tanja Oud; Jana Tuijtelaars; Jimmy Schenk; Frans Nollet; Merel-Anne Brehm (Health and Quality of Life Outcomes, 2023)
Abstract Background Orthosis satisfaction is an important outcome in assessing quality of care. However, no measurement specifically assessing orthosis satisfaction is available in the Dutch language. Therefore, the aim of this study was to translate the Client Satisfaction with Device (CSD) module of the Orthotics and Prosthetics Users’ Survey (OPUS) into Dutch, and to assess its content validity, structural validity and reliability in persons with chronic hand conditions. Methods The CSD was translated and cross-cultural adapted according to respective guidelines. To determine content validity, 10 chronic hand orthotic users and two professionals judged the relevance, comprehensibility, and comprehensiveness of the Dutch CSD (D-CSD). Thereafter, in a cross-sectional study, 76 persons were asked to complete the D-CSD twice, with a 2-week interval. Dimensionality of the D-CSD was examined by principal component analysis (PCA), and factor model fit was assessed by confirmatory factor analysis (CFA). Reliability was assessed as internal consistency and test-retest reliability, including the 95% limits of agreement (LoA), the standard error of measurement (SEM) and smallest detectable change (SDC). Results The D-CSD items and response options were deemed relevant and comprehensible. After adding an item on cleaning the orthosis, content validity was judged sufficient. PCA indicated a one-factor model, which was confirmed by CFA. We found good internal consistency (Cronbach’s alpha = 0.82; 95%CI 0.75–0.87), and moderate to good test-retest reliability (ICC = 0.81; 95%CI 0.71–0.87). There was no difference between the mean D-CSD score at test (26.8 points) and retest (25.9 points) (mean (SD) difference: 0.86 points (4.00); 95%CI -0.06-1.79; p = 0.07). The 95% LoA were −6.99 to 8.71, and the SEM and SDC were 2.88 and 7.98 points, respectively. Conclusions Based on sufficient content and structural validity, and good reliability, we consider the D-CSD a useful tool to evaluate orthosis satisfaction in persons with chronic hand conditions on group level. Because of a relatively high SDC, sensitivity to detect changes over time on individual level is limited. Study registration number NCT05320211.